2014
DOI: 10.1007/s00432-014-1584-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of ALK rearrangements in primary lung adenocarcinoma with identified EGFR and KRAS status

Abstract: The ALK rearrangements are independently associated with younger age and the EGFR wild type. The EGFR mutations and the ALK rearrangements are rarely coexistent. The ALK rearrangements and the KRAS mutations are mutually exclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…Previous studies have reported that the frequency of the ALK rearrangements in NSCLCs using FISH ranged from 3 to 13% [34,35,36,37,38]. Values of 3-11% ALK positivity were found for the Chinese population in several studies [22,39,40,41,42], with the inconsistency reported resulting from factors including the methodology used to detect the ALK rearrangements and the patients enrolled in the studies. Our results for ALK rearrangements are consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that the frequency of the ALK rearrangements in NSCLCs using FISH ranged from 3 to 13% [34,35,36,37,38]. Values of 3-11% ALK positivity were found for the Chinese population in several studies [22,39,40,41,42], with the inconsistency reported resulting from factors including the methodology used to detect the ALK rearrangements and the patients enrolled in the studies. Our results for ALK rearrangements are consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have identified the associations between EGFR mutations and the predominant subtypes subsequent to the publication of the novel IASLC/ATS/ERS classification. Wang et al (26) examined 332 patients with primary LAC, and 149 patients (44.9%) were found to harbor EGFR mutations; the EGFR mutation rate was significantly increased in the papillary predominant subtype compared with the solid predominant subtype with mucin production (P=0.008). Song et al (24) reviewed 161 patients who underwent surgical resections, and EGFR mutation was examined in 67 cases (41.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (26) did not identify any significant differences in histological subtypes between the KRAS mutations and the wild-types; whereas, Yoshizawa et al (14) and Kakegawa et al (28) indicated that KRAS mutations were significantly associated with adenocarcinoma of mucinous tumor subtypes (P<0.001). Rekhtman et al (29) showed that KRAS mutations occurred more often in adenocarcinomas with a solid growth pattern (P=0.022).…”
Section: A B C D E Fmentioning
confidence: 97%
See 1 more Smart Citation
“…EML4-ALK rearrangement was reported as a relatively low frequent rearrangement ranging from 1.5% to 6.7% among unselected Caucasian NSCLC patients (14)(15)(16)(17). It seems to have higher frequency in Asian population, and was reported as high as 5.1-10% (18)(19)(20)(21). Part of the explanation was that in those studies, patients were selected from EGFR wild population.…”
Section: Discussionmentioning
confidence: 99%